The Incorporation of Digital Literacy in EFL Learning Materials for Senior High School Students - Agusprayuningtyas, Nadila Farah; Iskandar, Ifan; Dewanti, Ratna (Lembaga Penelitian dan Pengabdian kepada Masyarakat dan Program Studi Pendidikan Bahasa Inggris Fakultas Bahasa dan Seni Universitas Negeri Jakarta, 2022)
Digital literacy is an important ability to have to succeed in today's era where almost everything is surrounded by digital technologies, tools, services, and so on. This study aims to investigate to what extent digital literacy is incorporated in EFL learning materials for senior high school students, and to describe how digital literacy is incorporated in EFL learning materials. This qualitative study uses content analyses in analyzing the 36 learning materials that have been collected from 4 different public senior high schools in the East Jakarta area from 4 different teachers. This present study found that digital literacy is not yet maximally incorporated into the learning materials. Out of 36 English learning materials, only 16 English learning materials seem to be incorporated with digital literacy indicators, while some others didn't even incorporate digital literacy at all. Digital literacy in learning materials is incorporated in many ways; instruction (43 occurrences), task (31 occurrences), text (8 occurrences), and last is the provision of links (3 occurrences).